Development of the MetFlex Index™: associations between cardiometabolic risk factors and fitness using a novel approach with blood lactate - Jasker, Bryan; Dodd, Daniel; Peek, Clara B.; Griffith, Garett J. (Frontiers in Physiology, 2025)
IntroductionCardiometabolic health is declining in the U.S. and anticipated to worsen over the next 30 years. Measurements of cardiometabolic health include blood metabolite profiles. One such metabolite is blood lactate. Lactate assessment is common in critical care and performance settings but less frequently used for the general population. The delayed onset of lactate accumulation during exercise may be an indicator of cardiometabolic health. Assessing lactate during a submaximal exercise test may assist in describing cardiometabolic health status in terms of metabolic fitness and metabolic flexibility.ObjectivesTo introduce the MetFlex Index™ (MFI), a novel, scalable exercise-based and marker of cardiometabolic health, and to characterize its associations with routinely assessed cardiometabolic health risk factors.MethodsParticipants completed a submaximal test on a commercial stationary cycle following assessments of body composition, anthropometrics, vital signs, and a blood draw. Lactate was collected at each stage and the 1st and 2nd lactate thresholds were described. The MFI was calculated by using the power, in Watts, attained at the 1st lactate threshold relative to the participant’s Body Mass Index (BMI).ResultsData were collected on 827 participants (43 ± 13 years, 67% male, 72% overweight or obese). MFI peaked in the 30–39 year old cohort and decreased in subsequent decades. MFI was negatively associated with most markers of anthropometry, body composition, blood pressure, and was not associated with most blood metabolites.DiscussionThe MetFlex Index™ is a novel exercise-based approach using blood lactate to characterize skeletal muscle metabolism and is associated with several cardiometabolic health indices.